1989
DOI: 10.1111/j.1699-0463.1989.tb00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagen induced arthritis as an experimental model for rheumatoid arthritis

Abstract: Collagen induced arthritis as an experimental model for rheumatoid arthritis; immunogenetics, pathogenesis and autoimmunity. APMIS 97. [575][576][577][578][579][580][581][582][583][584] 1989.The type I1 collagen (CII) induced arthritis animal model (CIA) provides opportunities to study the nature ofautoimmune reactions leading to arthritis and may be used as a model for rheumatoid arthritis (RA). Thus, in similarity with RA, the CIA model, when induced with autologous CII, shows a chronic and progressive disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 66 publications
0
71
0
1
Order By: Relevance
“…The susceptibility and resistance of DBA͞1j and SWR͞j, respectively, to the induction of CIA is well documented (9,10,15). As with previously published data, the DBA͞1j mice in these experiments had an incidence of 100% whereas the SWR͞j mice were completely resistant (0% incidence).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The susceptibility and resistance of DBA͞1j and SWR͞j, respectively, to the induction of CIA is well documented (9,10,15). As with previously published data, the DBA͞1j mice in these experiments had an incidence of 100% whereas the SWR͞j mice were completely resistant (0% incidence).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic crosses between susceptible and resistant inbred mouse strains have demonstrated that CIA is inherited in most inbred strains as a polygenic, dominant trait (9,10). Several investigators have explored the role of the murine major histocompatibility complex (Mhc or H-2) in CIA development by immunization of congenic and inbred strains with heterologous and homologous CII (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Arthritis is induced in susceptible strains of rats and mice by immunisation with type II collagen in incomplete Freund's adjuvant (IFA) or complete Freund's adjuvant (CFA), respectively (Holmdahl et al, 1989;Trentham, 1982). Both T helper (Th) 1 and (Th17) responses are induced in CIA, but Th17 cells appear to play the dominant pathological role (Murphy et al, 2003).…”
Section: Models Commonly Used For Drug Testing (A) Collagen-induced Amentioning
confidence: 99%
“…CIA is elicited through intradermal injection of chick or bovine type II collagen (CII) in the presence of Freund's complete adjuvant into genetically susceptible mice [56]. In initial studies, i.p.…”
Section: Mechanistic Lessons From Animal Modelsmentioning
confidence: 99%